2022
DOI: 10.1371/journal.ppat.1010820
|View full text |Cite
|
Sign up to set email alerts
|

miRNA let-7 family regulated by NEAT1 and ARID3A/NF-κB inhibits PRRSV-2 replication in vitro and in vivo

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically devastating diseases affecting the swine industry worldwide. To investigate the role of miRNAs in the infection and susceptibility of PRRS virus (PRRSV), twenty-four miRNA libraries were constructed and sequenced from PRRSV-infected and mock-infected Porcine alveolar macrophages (PAMs) of Meishan, Landrace, Pietrain and Qingping pigs at 9 hours post infection (hpi), 36 hpi, and 60 hpi. The let-7 family miRNAs were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Meng cloned the GP5 gene into a eukaryotic expression plasmid under the control of the cytomegalovirus early promoter to prepare a DNA vaccine, which could induce the production of antibodies after immunization of piglets [ 41 ]. More and more studies showed that miRNAs could be used to treat PRRS [ 42 44 ]. In our research, intramuscular injection of pEGFP-N1-miR-320 could reduce the replication of PRRSV in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Meng cloned the GP5 gene into a eukaryotic expression plasmid under the control of the cytomegalovirus early promoter to prepare a DNA vaccine, which could induce the production of antibodies after immunization of piglets [ 41 ]. More and more studies showed that miRNAs could be used to treat PRRS [ 42 44 ]. In our research, intramuscular injection of pEGFP-N1-miR-320 could reduce the replication of PRRSV in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that let-7 plays a key role in regulating immune responses ( 92 , 93 ). Upon PRRSV infection, the expression of let-7 family is significantly upregulated, and the let-7 family inhibits PRRSV proliferation via directly targeting both the PRRSV-2 genome and IL-6 ( Figure 2A , Table 1 ) ( 16 ). More importantly, let-7 family can remarkably decrease PRRSV infection and associated pathological changes both in vitro and in vivo , suggesting that the let-7 family may serve as promising therapeutic targets for PRRS.…”
Section: Roles Of Mirnas In Host Response To Prrsv Infectionmentioning
confidence: 99%
“…Mature miRNAs, within the RISC, induce translational repression and deadenylation of target mRNA. Numerous host miRNAs have demonstrated influence on various processes, including pathogenic diseases and host immunity ( 4 , 15 , 16 ). Therefore, understanding the biological functions of miRNAs and the mechanism of their actions will be instrumental in drug development and disease control.…”
Section: Introductionmentioning
confidence: 99%
“…The let-7 family consists of let-7a, let-7c, let-7d, let-7e, let-7f, let-7g, let-7i, and miR-98. A recent study has demonstrated that PRRSV-2 infection leads to a marked change in the expression of the let-7 family, which subsequently targets PRRSV-2 genomic RNAs, effectively inhibiting their replication [ 121 ]. Moreover, the expression of ARID3A transcription factor down-regulates let-7a and let-7f expression, thereby significantly promoting PRRSV-2 replication.…”
Section: Ncrna During Porcine Virus Infectionmentioning
confidence: 99%